Physical Factors in the Treatment of Chronic Venous Insufficiency of the Lower Extremities - Aleksandr Derinov (Journal of Global Pharma Technology, 2016)
Trophic ulcers are one of the most severe complications of chronic venous diseases, leading to functional insufficiency of the lower extremities and a sharp decline in the life quality. Complex of preoperative preparation and combination with various methods of surgical correction are essential in this case. Higher results can be obtained with combined application of several techniques. Topical application of combined low-intensity laser radiation and micro dispersed drug irrigation is a pathogenetically substantiated non-invasive method of conservative treatment and preoperative preparation of trophic ulcers in patients of the C6 class.Keywords: Bactericidal therapy, Pain syndrome, Varicose veins, Trophic ulcers.